2009
DOI: 10.1007/s00521-009-0288-5
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey on functional link neural networks and an adaptive PSO–BP learning for CFLNN

Abstract: Functional link neural network (FLNN) is a class of higher order neural networks (HONs) and have gained extensive popularity in recent years. FLNN have been successfully used in many applications such as system identification, channel equalization, short-term electricload forecasting, and some of the tasks of data mining. The goals of this paper are to: (1) provide readers who are novice to this area with a basis of understanding FLNN and a comprehensive survey, while offering specialists an updated picture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 121 publications
(142 reference statements)
0
59
0
1
Order By: Relevance
“…It is shown that the performance of functional-link NN is similar to that of a NN but with faster convergence and lesser computational complexity. Moreover, a comprehensive survey on various applications of functional-link NN has been proposed in [12].…”
Section: Chih-hong Linmentioning
confidence: 99%
“…It is shown that the performance of functional-link NN is similar to that of a NN but with faster convergence and lesser computational complexity. Moreover, a comprehensive survey on various applications of functional-link NN has been proposed in [12].…”
Section: Chih-hong Linmentioning
confidence: 99%
“…In most previous researches, the learning algorithm used for training the FLNN is the Backpropagation (BP) [8,16,22,23,[25][26][27]. BP learning is developed by Rumelhart [28] in which the network is provided with examples of the inputs and desired outputs to be computed, and then the error (difference between actual and expected results) will be calculated.…”
Section: Flnn Learning Schemementioning
confidence: 99%
“…Another limitation of BP-learning algorithm inherit by FLNN-BP is that, the network is very dependent on the choices of initial values of the weights set as well as the parameters in the algorithm such as the learning rate and momentum [8] which make it not very easy to meet the desired convergence criterion during the training.…”
Section: Flnn Learning Schemementioning
confidence: 99%
See 2 more Smart Citations